ANALYTICAL AND NUMERICAL STUDY OF RESONANCE PHENOMENON OVER SUBMERGED BREAKWATER - Jonathan, Gabriel
Wave resonance phenomena in a basin can cause enormous damage to the environment. The natural resonant period of the basin is one of the primary causes of the resonance phenomenon. The resonance phenomenon is caused by external forces coming into the basin with a similar period as the natural period of the basin. One way to mitigate this resonance phenomenon is to construct a breakwater. We will observe the analytical natural period of basins with one block of rectangular submerged breakwater with rough and smooth surface, also basins with two blocks of smooth rectangular submerged breakwater. The analytical natural period is obtained using the linear shallow water equation (LSWE). We will conduct numerous numerical simulations to confirm and detect the existence of the resonance phenomenon. For basins with rough bottom surface, we will also calculate the optimal friction coefficient required to prevent the resonance occurrences.